Formal instruction by Song for English Learners in SMP IT Darul Hasan while Pandemic Era - Muhriza, Fatma (Proceeding of International Conference on Language Pedagogy (ICOLP), 2021)
This research was examined to help the English teacher in Junior high school especially, while pandemic Covid-19 more dilate over the world. The pandemic that has hit the world in the last 3 years, it gas given much attention from all elements in the world generally, the side of education do need new innovations to keep advancing the target of education, so one of thing teachers do at SMP IT Darul Hasan Kota Padangsidimpuan to overcome the problem have tried carry out formal instruction in achieving good English grammar according to their target and age, namely through songs with grammar elements according to the lesson curriculum in social media flat form. This research have done for treat in 7 class SMP IT Darul Hasan Kota Padangsidimpuan that consist of 25 students randomly. The three classes have a different acquisition in English subject, again which the students in 7d, 7e, and 7f. So, in my conclusion that formal instruction by song in Junior high school SMP IT Darul Hasan Kota Padangsidimpuan has given a positive effect.